Pengaruh Kualitas Produk dan Pengalaman Pelanggan Terhadap Loyalitas Pelanggan Aplikasi Netflix di Kecamatan Kalianda: Penelitian - Siti Berliana Nuraziza Pubaya; Tamam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of Product Quality (X₁) and Customer Experience (X₂) on Customer Loyalty (Y) of the Netflix application among Generation Z in Kalianda District, both partially and simultaneously. This type of research is quantitative using an explanatory approach, and the sampling technique is non-probability sampling with a purposive sampling method. The sample in this study consisted of 140 respondents in Kalianda District who have used Netflix services. Data collection was carried out through the distribution of online questionnaires based on a Likert scale, and the data obtained were analyzed using SPSS software version 26. Based on the results of the partial analysis (t-test), it was found that the Product Quality variable has a positive but insignificant effect on Customer Loyalty, with a calculated t of 1.490 < t-table 1.658 and a significance value of 0.140 > 0.05. The Customer Experience variable has a positive and significant effect on Customer Loyalty, with a calculated t of 6.871 > t-table 1.658 and a significance value of 0.000 < 0.05. While the results of the simultaneous test (F-test) show that the calculated F is 58.519 > F-table 3.06 with a significance level of 0.000 < 0.05, and degrees of freedom df1 = 2 and df2 = 137.